Comorbid Personality Disorders in Individuals With an At-Risk Mental State for Psychosis: A Meta-Analytic Review - Boldrini, Tommaso; Tanzilli, Annalisa; Pontillo, Maria; Chirumbolo, Antonio; Vicari, Stefano; Lingiardi, Vittorio (Frontiers in Psychiatry, 2019)
Abstract Increasing evidence shows that personality pathology is common among patients at enhanced clinical high risk (CHR) of psychosis. Despite the important impact that this comorbidity might have on presenting high-risk psychopathology, psychological functioning, and transition to full psychotic disorders, the relationship between personality syndromes and CHR states has received relatively little empirical attention. The present meta-analytic review aimed at (1) estimating the prevalence rates of personality disorders (PDs) in individuals at clinical high risk of first-episode psychosis and (2) examining the potential role of personality disorders in predicting transition to psychosis. The systematic search of the empirical literature identified 17 relevant studies, examining a total of 2,144 CHR individuals. Three distinct meta-analyses were performed to provide prevalence estimates of PDs in the CHR population. The first and more comprehensive meta-analysis focused on any comorbid PD (at least one diagnosis), the second one focused on schizotypal personality disorder (SPD), and the last one focused on borderline personality disorder (BPD). Moreover, a narrative review was presented to define the predictive role of the personality of CHR patients in promoting more severe outcomes. The findings showed that the prevalence rate of comorbid personality diagnoses in CHR patients was 39.4% (95% CI [26.5%–52.3%]). More specifically, 13.4% (95% CI [8.2%–18.5%]) and 11.9% (95% CI [0.73%–16.6%]) of this clinical population presented with SPD and BPD, respectively. Finally, the studies examining the effects of baseline personality diagnoses on conversion to psychosis showed contradictory and insufficient results concerning the potential significant impact of SPD. Conversely, no effect of BPD was found. The present meta-analytic review indicated that the CHR population includes a large subgroup with serious personality pathology, that may present with attenuated psychotic symptoms conjointly with distinct and very heterogeneous personality features. These findings support the need for better understanding core psychological characteristics of CHR patients and differentiating aspects of personality that could have relevant clinical implications in promoting individualized preventive interventions and enhancing treatment effectiveness.